Carbohydrates Metabolic Signatures in Immune Cells: Response to Infection - Awad, Kareem; Maghraby, Amany Sayed; Abd-Elshafy, Dina Nadeem; Bahgat, Mahmoud Mohamed (Frontiers in Immunology, 2022)
Introduction: Metabolic reprogramming in immune cells is diverse and distinctive in terms of complexity and flexibility in response to heterogeneous pathogen stimuli. Aim: We aim to study the carbohydrate metabolic changes in the immune cells during different types of infections and metabolic disorders. This could help to build reasonable strategies when understanding the diagnostics, prognostics and biological relevance of immune cells under alternative metabolic burdens. Method: Searching and analyzing published peer reviewed papers on the immune cells metabolism of a single pathogen infection from the four known types (bacteria, fungi, parasites and viruses) as well as most common metabolic disorders were conducted. Out of 134 selected papers based on the PIC algorithm (pathogen type/ immune cell/ carbohydrate metabolism), 30 explored immune cells metabolic changes during well studied bacterial infections, 17 during fungal infection of known medical importance, 12 and 57 of parasitic and viral infections respectively. Results: While carbohydrate metabolism in the immune cells is signed by the glycolysis shift during bacterial or viral infection, it is widely evident that effector surface proteins are expressed on the surface of parasites and fungi to modulate metabolism in these cells. Conclusion: Carbohydrate metabolism in the immune cells can be categorized according to the pathogen or the disease type. Accordingly this classification can be used to adopt new strategies in diagnosis and treatment.